South Africa : Financial Sector Assessment Program-Detailed Assessment of Implementation on the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses findings of the Detailed Assessment of Implementation on the IOSCO (International Organization of Securities Commissions) Objectives and Principles of Securities Regulation in South Africa. Although South Africa's level of implementation of the IOSCO principles is complete in several areas, there is room for enhancement. The legal framework is robust and provides the authorities with broad supervisory, investigative, and enforcement powers. There are arrangements for on-site and off-site monitoring of regulated entities. The powers to cooperate with domestic and foreign counterparts are extensive. Accounting and auditing standards are high, as is the disclosure regime that applies to listed companies in practice.